2020
DOI: 10.1002/ijfe.1924
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic dependence and extreme risk comovement: The case of oil prices and exchange rates

Abstract: This article aims at investigating the dynamic dependence and extreme risk comovement of oil price and exchange rates in seven oil‐importing and seven oil‐exporting countries. For this purpose, we use six representative time‐varying copula models and four kinds of tail dependences to assess the downside and upside conditional value‐at‐risk measures (CoVaRs). Our findings indicate that the dependence of crude oil returns and exchange rates is negative for most pairs, that is, the rise (fall) in oil prices was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 61 publications
(125 reference statements)
2
4
0
Order By: Relevance
“…Furthermore, the corresponding Kendall dependence is weak for all oil-exchange-rate pairs; nevertheless, the oil exporters' exchange rates have relatively stronger links with crude oil prices than the oil importers. This finding is almost consistent with the overall sample results of Liu et al [43]. The higher oil prices can transfer the wealth from oil importers to oil exporters, leading to the devaluation of the currencies of oil importers; however, the currencies of oil exporters will be appreciated instead.…”
Section: Estimation Of Time-varying Factor Copula Modelsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the corresponding Kendall dependence is weak for all oil-exchange-rate pairs; nevertheless, the oil exporters' exchange rates have relatively stronger links with crude oil prices than the oil importers. This finding is almost consistent with the overall sample results of Liu et al [43]. The higher oil prices can transfer the wealth from oil importers to oil exporters, leading to the devaluation of the currencies of oil importers; however, the currencies of oil exporters will be appreciated instead.…”
Section: Estimation Of Time-varying Factor Copula Modelsupporting
confidence: 91%
“…We find that the oil exporters' conditional dependence characteristics for the oilexchange-rate pairs are almost the same as in the Copula-GARCH model shown in Liu et al [43]; nevertheless, we have identified a much larger dependence magnitude between the financial markets in consideration of respective common factors. The factor copula model can capture the relatively greater variation in the market dependence after the 2008 global financial crisis and in the COVID-19 era.…”
Section: Dynamic Dependence For Oil Exporterssupporting
confidence: 70%
See 2 more Smart Citations
“…In an early study, Hamilton (1983) shows that rising oil price is a driving force of the U.S. economic recession. Since then, numerous researchers have discovered that oil price can significantly impact macroeconomic activity and the financial market, including economic growth (Känzig, 2021; Kilian, 2009), inflation (Gong et al, 2020; Wen et al, 2019), exchange rate (Liu et al, 2021; Živkov et al, 2019), and stock return (Bouri et al, 2017; Kwon, 2022; Wang & Wang, 2019). Besides, it is generally known that many firms utilize oil as a significant production factor.…”
Section: Introductionmentioning
confidence: 99%